In-Person Versus Telehealth for Concussion Clinical Care in Adolescents: A Pilot Study of Therapeutic Alliance and Patient Satisfaction. Issue 4 (26th July 2022) - Elbin, R. J.; Stephenson, Katie; Lipinski, Damon; Maxey, Kristin; Womble, Melissa N.; Reynolds, Erin; Covert, Kayla; Kontos, Anthony P.
Abstract : Objective: To conduct a pilot study of caregiver ratings of therapeutic alliance and patient satisfaction outcomes between telehealth and in-person concussion clinical care in male and female adolescent athletes. Setting: Outpatient neuropsychology concussion clinic. Participants: Fifteen patients (aged 15.40 ± 1.35 years; 33% female) with a concussion and their accompanying caregivers ( n = 15; 87% female) were randomly assigned to an in-person clinic visit and 15 patients (aged 15.13 ± 1.25 years; 40% female) with a concussion and their accompanying caregivers ( n = 15; 73% female) were randomly assigned to a telehealth clinic visit. Design: A prospective, randomized design. Main Measures: Therapeutic alliance and patient satisfaction scores. Results: Therapeutic alliance scores were not significantly different for patients in the in-person or telehealth setting, and caregiver therapeutic alliance scores were significantly higher for the in-person condition than for the telehealth condition. There were no significant differences between in-person and telehealth session satisfaction scores for patients on depth, smoothness, positivity, arousal, and bad-good outcomes. Patient and caregiver satisfaction with the clinical setting was high (ie, General Endorsement). Conclusion: Telehealth is feasible for assessing and interpreting clinical concussion examination, interview, and neurocognitive findings, which are perceived by patients and their caregivers to be comparable with in-person care. Positive satisfaction scores also serve to reinforce the need for healthcare providers to seek ways to actively engage with patients and their caregivers through elements of communicative skills such as active listening, building patient rapport, encouraging patient autonomy, and providing an adequate amount of time for interaction and questions. Telehealth for concussion care is increasing in implementation across health systems, and demand is likely to grow in light of the current COVID-19 pandemic and advances in telehealth delivery.